Conceptual Model of User Adaptive Enterprise Application - Inese Šūpulniece; Jānis Grabis (Complex Systems Informatics and Modeling Quarterly)
The user adaptive enterprise application is a software system, which adapts its behavior to an individual user on the basis of nontrivial inferences from information about the user. The objective of this paper is to elaborate a conceptual model of the user adaptive enterprise applications. In order to conceptualize the user adaptive enterprise applications, their main characteristics are analyzed, the meta-model defining the key concepts relevant to these applications is developed, and the user adaptive enterprise application and its components are defined in terms of the meta-model. Modeling of the user adaptive enterprise application incorporates aspects of enterprise modeling, application modeling, and design of adaptive characteristics of the application. The end-user and her expectations are identified as two concepts of major importance not sufficiently explored in the existing research. Understanding these roles improves the adaptation result in the user adaptive applications.